Patients' perspective of functional outcome after elective abdominal aortic aneurysm repair: A questionnaire survey - Khan, Junaidalam; Mazari, Fayyaz Ali Khan; Abdul Rahman, Mohd Norhisham Azmi; Mockford, Katherine; Chetter, Ian Clifford; McCollum, Peter Thomas (Elsevier, 2011)
Background: To evaluate patients’ awareness, functional outcome, and satisfaction after abdominal aortic aneurysm (AAA) repair. Methods: A study-specific questionnaire was developed with collaboration of a multidisciplinary team. Lists of patients who underwent elective open AAA repair and endovascular aneurysm repair (EVAR) between January 2006 and December 2008 were obtained from the departmental database and cross-checked against hospital database for survival status. Emergency AAA repairs were excluded. Study questionnaires were posted to 138 patients (113 open, 25 EVAR) with selfaddressed stamped return envelopes. Statistical analysis was performed using SPSS v16.0. Results: Response rate was 89% (n ¼ 123; 102 open, 21 EVAR). Seventy-one percent (n ¼ 88) were unaware of this condition before diagnosis. Ninety-seven percent (n ¼ 120) indicated their understanding of the need for surgery. Ninety-two percent (n ¼ 113) stated that the operation was adequately explained to them. Ninety percent (n ¼ 111) reported full recovery after surgery, with 60% (n ¼ 74) recovering within 6 months. Eighty-seven percent (n ¼ 108) were satisfied with the overall experience, and 85% (n ¼ 105) stated that they would recommend the operation to family and/or friends if required. Conclusions: There is a lack of awareness regarding AAA in elderly population. However, after being diagnosed, patients understand the implications and are satisfied with the overall results and would recommend AAA repair to family and/or friends if required.